Integration of Wind and Solar Energy with Fuzzy Logic Control MPPT for Grid-Connected Hybrid Renewable Power Generation - Abhimanyu Kumar; Ambrish Pati Tripathi; Brijesh Kumar Pandey; Rohit Gedam (International Journal of Electrical Power and Machine Systems, 2025)
The utilization of renewable energy sources, such as wind and solar energy, has gained significant attention due to their eco-friendly nature and sustainability. This research paper explores the mechanisms behind wind generation and its integration with solar power, focusing on the adoption of Fuzzy Logic Control (FLC) for Maximum Power Point Tracking (MPPT) in a grid-connected hybrid renewable energy system. The paper outlines the principles of wind and solar energy conversion, the working of wind turbines, and the role of FLC in improving MPPT efficiency. Furthermore, the study presents the objectives of developing and simulating a hybrid power system that connects to the grid through an inverter capable of stabilizing the DC bus voltage during variable energy conditions. The application of fuzzy controllers for improved power quality and performance is investigated. The simulation and result analysis highlight the advantages of FLC-based MPPT in enhancing the efficiency and power output of the integrated wind-solar system. This research aims to contribute to the advancement of knowledge in renewable energy utilization and the implementation of intelligent control techniques for efficient power generation.
Keywords: Grid-Connected Hybrid Renewable System; Simulation; Solar Energy; Wind Energy; fuzzy logic control; maximum power point tracking; power quality